Complete remission in a patient with metastatic gastric cancer receiving tislelizumab combined with chemotherapy: a case report - Zhu, Zhe; Dai, Pei-Lin; Han, Shuai; Qiu, Enming; Wang, Yu; Li, Zhou (Frontiers in Oncology, 2023)
The prognosis for patients with advanced gastric cancer (AGC) is poor, with limited treatment options available due to the difficulty of resection. In recent years, chemotherapy and immunotherapy for AGC have shown promising efficacy. However, there is a controversy regarding the surgery of primary tumors and/or metastases in patients with stage IV gastric cancer after systematic therapy. Here, we present a 63-year-old retired female of AGC with supraclavicular metastasis. After receiving 8 cycles of capecitabine and oxaliplatin (XELOX) in combination with tislelizumab, the patient achieved complete remission (CR). No evidence of recurrence was identified during follow-up. To the best of our knowledge, this is the first case of AGC with supraclavicular metastasis who achieved CR after treatment with tislelizumab. The mechanism of CR was discussed by genomic and recent clinical studies. The results indicated that programmed death ligand-1 (PD-L1) combined positive score (CPS) ≥5 may serve as a clinical indication and standard for chemo-immune combination therapy. In combination with other similar reports, patients with microsatellite instability-high/defective mismatch repair (MSI-H/dMMR), tumor mutational burden-high (TMB-H), and positive PD-L1 had better sensitivity to tislelizumab. The patient recovered successfully except for symptoms of gastrointestinal hemorrhage during treatment, which may be associated with the treatment cycle and age. Immunotherapy with tislelizumab has been well-established in the treatment of malignant melanoma, lung cancer, and clear-cell kidney cancer, but its efficacy and safety for esophageal and gastric cancers remain to be validated. The CR of our patient suggested the prospects of tislelizumab in the immunotherapy of gastric cancer. Additionally, a watch-and-wait (WW) method was offered for patients with AGC who achieved complete clinical remission (CCR) after immune combination therapy if the patient was older or in poor physical condition.